2024
DOI: 10.1093/geroni/igae026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Self-Reported and Capacity-Based Measures of Mobility in Community-Dwelling Older Adults in Nigeria: The Mediating Role of Age, Cognitive Status, and Chronic Conditions

Michael E Kalu,
Daniel Rayner,
Ernest C Nwachukwu
et al.

Abstract: Background and Objectives Although the association between self-reported and capacity-based mobility outcomes is prominently researched, the pathways through which self-reported measures affect capacity-based measures remains poorly understood. Therefore, our study examines the association between self-reported and capacity-based mobility measures and explores which mobility determinants mediate the association in Nigerian community-dwelling older adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Four empirical articles on psychometrics and building research capacity for aging research and practice in Africa follow. In the first, Kalu et al (2024) compared self-reported and capacity-based measures of mobility in community-dwelling older adults and explored age, cognitive status, and chronic conditions as mediators. The relationship between self-reported and capacity-based mobility outcomes in Nigerian older adults was lower than those in developed countries.…”
Section: Psychometrics and Building Research Capacitymentioning
confidence: 99%
“…Four empirical articles on psychometrics and building research capacity for aging research and practice in Africa follow. In the first, Kalu et al (2024) compared self-reported and capacity-based measures of mobility in community-dwelling older adults and explored age, cognitive status, and chronic conditions as mediators. The relationship between self-reported and capacity-based mobility outcomes in Nigerian older adults was lower than those in developed countries.…”
Section: Psychometrics and Building Research Capacitymentioning
confidence: 99%